Ending a diagnostic odyssey—The first case of Takenouchi–Kosaki syndrome in an African patient. Issue 4 (2nd March 2021) - Flynn, Kaitlyn; Feben, Candice; Lamola, Lindiwe; Carstens, Nadia; Krause, Amanda; Lombard, Zané
Abstract: First reported case of Takenouchi–Kosaki syndrome in an African patient with a de novo likely pathogenic missense variant identified in the CDC42 gene. Abstract : First reported case of Takenouchi–Kosaki syndrome in an African patient with a de novo, likely pathogenic missense variant identified in the CDC42 gene.